Tantangan dan Peluang Implementasi Smart Governance di Indonesia: Tinjauan Komparatif Literatur untuk Konteks Pekanbaru - Alif Addarisalam; Annisa Supriana; Bambang Setia Budi; Raihan Ardyansyah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The concept of smart governance has become increasingly crucial in supporting public sector reform through digital transformation. This study aims to identify the major challenges and opportunities in implementing smart governance in Indonesia by conducting a comparative review of academic journal literature and contextualizing the findings to the case of Pekanbaru. The analysis reveals three critical challenges: uneven digital infrastructure, low digital literacy among civil servants, and fragmented regulations and inter-agency coordination. On the other hand, the review also identifies opportunities in improving service quality and expanding citizen participation through digital platforms. Contextual discussion highlights how these findings reflect the actual conditions in Pekanbaru, which, despite its ambition to become a smart city, still struggles with systemic barriers. The study concludes with practical recommendations for the Pekanbaru city government, emphasizing the importance of capacity building, system integration, and inclusive public engagement. This review also serves as a foundation for future empirical research to validate the findings and enrich local digital governance strategies.